Habitus Masyarakat Lokal Desa Temajuk dalam Mengadaptasi Perkembangan Pariwisata - Aan Khosihan (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2021)
The development of tourism has many impacts on society including the habitus of local communities. In simple terms, it can be understood that the habitus is a system of habits that has been internalized in people's lives. This study aims to see the community's habitus in the midst of tourism development in Temajuk Village, Paloh District, Sambas Regency. This research is a qualitative study using primary interview data collection methods. Through the habitus concept of Pierre Bourdieu, there is a community of Temajuk village that intersects with the development of tourism which can be seen from the aspects of knowledge, understanding, perceptions, values, and actions that are internalized in people's daily lives.